The Ricardian equivalence hypothesis in ASEAN-3 countries - Abd Rahman, Muhammad Daaniyall (2012)
This study is aimed to examine the existence of Ricardian equivalence hypothesis in ASEAN-3 countries namely Indonesia, Malaysia, and Thailand. By using data from 1971 to 2005, Autoregressive Distributed Lag (ARDL) Bounds test approach was emplyed on Bernheim (1987) and Giorgioni and Holden (2003) models. Furthermore, the effect of temporary and permanent government spending on private consumption was also examined. Finally, we analyze the effect of government debt on private consumption in contingency on the level of debt. From the results, it can be concluded that the Ricardian equivalence hypothesis is rejected in short run for Indonesia and Malaysia whereas the in long run the hypothesis possibly existed. For Thailand, Ricardian equivalence hypothesis is denied in long run while holds in short run. The effect of substitutability and complementarity of government spending and private consumption can be found in the estimations. Generally, Indonesia government spending likely to be substitute to private consumption due to negative relationship majorly found. On the other hand, Malaysia government spending is pertinent as complementary to private consumption rather than substitute. For Thailand case, the government spending is substantially insignificant to influence the private consumption except for positive permanent government spending effect. In sum, Indonesia domestic debt has negative impact on private consumption while the foreign debt found to be insignificant. The interaction of the domestic debt dummy also proves the sensitivity of private consumption on domestic debt compares to insignificant foreign debt interaction. In Malaysia, the domestic debt has positive impact on private consumption especially in the long run. The impact of foreign debt found to be negative. Meanwhile, the dummy debts interaction is significant only for foreign debt which indicates the influence of external factors such as foreign exchange. For Thailand, the domestic debt is positively influence the private consumption whereas the foreign debt reacts differently. However, the dummy interaction of the debt components is thoroughly insignificant.